Dinamika Motivasi, Kesempatan dan Kemampuan Masyarakat Lokal dalam Mengembangkan Desa Wisata Batu Cermin - Andriano Calrinto Mami; Dewi Sartika Umul (JURNAL AKADEMISI VOKASI, 2025)
This study aims to analyze the dynamics of motivation, opportunities and abilities of local communities in Batu Cermin Tourism Village as one of the tourist attractions in the Labuan Bajo Super Priority Destination. Using the MOA model approach (Motivativation, Opportunity, Ability), This study combines qualitative data from in-depth interviews with tourism actors and policy makers and quantitative data from questionnaires distributed to local communities. Using a mixed methods approach, The data was then analyzed using qualitative descriptive. The results of the study showed that the community has a fairly high motivation to be involved in the tourism sector, which is driven by the hope of improving the economy and preserving local culture. However, the opportunities that exist are still limited by policies and regulations between management parties, especially in Batu Cermin Cave which is the main asset of the Village. In terms of ability, the majority of the community feels that they have potential, but still need to increase capacity and capability through ongoing training. Therefore, strengthening local capacity and active community involvement are the keys so that Batu Cermin Tourism Village can develop into a sustainable and world-class tourism destination.